It's the Right Thing to Do: The Voices of Seven White Culturally Responsive Professors of Education - China M. Jenkins (Adult Education Research Conference, 2016)
This study explored the motivation of White educators to become culturally responsive, their processes of transformation and how they transformed self and pedagogy as a result.
Keywords: Culturally Responsive Teaching; Transformation; Motivation